Hyaluronic acid injection to restore the lost interproximal papilla: a systematic review. (19th May 2022) - Castro-Calderón, Adriana; Roccuzzo, Andrea; Ferrillo, Martina; Gada, Sneha; González-Serrano, José; Fonseca, Manrique; Molinero-Mourelle, Pedro
Abstract: Objectives: To assess the efficacy and safety of hyaluronic acid (HA) injections to restore the lost interproximal papilla. Materials and Methods: A systematic literature search was conducted in PubMed/MEDLINE, Scopus and Cochrane electronic databases with no time restriction up to September 2021. Any clinical study evaluating HA injection into the interproximal papilla loss Class I and II according to Norland & Tarnow, were included based on the following PICO questions (1) Are HA injections effective for the reconstruction of the interproximal papilla loss? (2) What are the side/adverse effects of using HA for the reconstruction of interproximal papilla loss? The risk of bias assessment was performed using the Cochrane Collaboration's the Newcastle Ottawa and Joanna Briggs institute tools. Results: A total of 1497 titles were retrieved. From these, eleven were included and underwent full data extraction. However, due to heterogeneity in the data among the included articles, a meta-analysis could not be performed. Three articles reported no-differences in term of papilla tip to contact point distance or the papilla fill reduction. Finally, five studies showed a reduction in the black triangle with a percentage range between 19 and 47%. Conclusion: The non-surgical use of HA injection seems to have a positive effect on the re-establishment of interproximal papilla lost. However post-operative complications might develop.